PROBLEMATIKA PENGAWASAN TERHADAP LEMBAGA NEGARA INDEPENDEN DALAM SISTEM KETATANEGARAAN: The Problematics of Oversight over Independent State Institutions within the Constitutional System - Usranda H. Hasan; Keysha Sandrina Damaianti Ulama; Devriyanti Saleh; Nurwita Ismail (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The development of Indonesia’s constitutional system after the reform era has been marked by the establishment of various independent state institutions aimed at strengthening the rule of law and democracy; however, their existence has generated problems concerning oversight in balancing independence and accountability. This study aims to analyze the oversight mechanisms of independent state institutions within Indonesia’s constitutional system and to identify normative and structural challenges arising in practice. The research employs a normative legal method using statutory and conceptual approaches through library research on primary and secondary legal materials, analyzed qualitatively with a deductive method. The findings indicate that oversight of independent state institutions is conducted through internal and external mechanisms, including legislative, executive, judicial supervision, and public participation. Nevertheless, such oversight still faces issues of unclear authority boundaries, potential political intervention, and an underdeveloped legal framework, thus requiring a proportional and constitutional oversight model to ensure both independence and accountability.